دراسة سلوك المغذيات (SiO4-4, PO4-3,NO3-,NO2-,NH4+) المنحلة في الماء على طول تدرج الملوحة لمصب نهر السن (البحر الأبيض المتوسط – سوريا) - كراوي, حازم; درويش, فيروز; جولاق, سمر (Latakia University Journal -Basic Sciences Series, 2013)
تركزت الدراسة على تحديد أهم الخصائص الهيدروكيميائية لمياه منطقة مصب نهر السن عبر تحديد تركيز الشوارد المغذية (النترات والنتريت والأمونيوم والفوسفات والسيليكات) والعوامل المؤثرة عليها، فضلاً على تحديد الكلوروفيل aفي عينات مائية جمعت من عدة مواقع من منطقة مصب نهر السن خلال الفترة الممتدة بين آذار 2011 وشباط 2012. رصدت أعلى التراكيز للشوارد المغذية على مدار العام في نقطة المصب S0 وتقاربت مع تركيز الشوارد المغذية في المحطة S50 على مدار أشهر العام بسبب جغرافية منطقة مصب نهر السن، كما تناقص تركيز الشوارد المغذية مع الابتعاد عن نقطة المصب متوافقاً مع تدرج الملوحة خلال جميع الطلعات البحرية، إذ شكّلت نقطة المصب المصدر الرئيس للمغذيات التي يتم توزيعها إلى باقي المحطات. أبدت تراكيز الشوارد المغذية تدرجاً واضحاً خلال أشهر الشتاء امتد إلى بعد 3000 متر عن نقطة المصب، بينما امتازت أشهر الصيف بتدرج أقل امتداداً في تركيز الشوارد المغذية، إذ انحصرت منطقة التدرج ضمن - 200 500 متر الأولى. أظهرت الدراسة الإحصائية وجود علاقة معنوية عكسية بين تركيز المغذيات وملوحة المياه، كما ارتبطت المغذيات إيجابياً فيما بينها، إذ أظهرت النترات علاقة ارتباط معنوية مع الفوسفات والسيليكات، بينما كانت علاقة ارتباط النترات مع النتريت وارتباط الأمونيوم مع النتريت معنوية ولكنها أقل أهمية. The study, has Focused on determination of the most important hydrochemical characteristics of AL-sin estuary area via determining the concentration of nutrient ions (nitrate, nitrite, ammonia, phosphates and silicates) and the factors affecting them. In addition, determining chlorophyll a in water samples collected from several locations of that area during the period between March 2011 and February 2012 was done. The highest concentrations of nutrient throughout the year were reported at river estuary point (S0) and converged with nutrient concentrations in the station S50 because of the geographic nature of AL-sin estuary area. A depression in their concentrations was observed in the station distanced away from the river estuary point, compatible with salinity gradient. River estuary point (S0) formed the main source of nutrients that are distributed to the rest of the stations. Nutrient concentrations showed clear gradual depression during the winter months down to 3,000 meters from the estuary point, while the gradient in the summer months has less extension; It was within the first 200 - 500 meters. Statistical study revealed a significant negative relationship between the nutrient concentrations and water salinity and positive relationship between each other. The nitrate showed a significant correlation with phosphate and silicate, while the correlation between nitrite and nitrate and the correlation between nitrite and ammonia were significant but less important.